THE FUNCTION OF SLANG USED IN THE FATE AND FURIOUS MOVIE - Utami, Ni Made Verayanti; Ariyaningsih, Ni Nyoman Deni; Nadila, Ni Kadek Sinta Sri (LITERA : Jurnal Bahasa Dan Sastra, 2021)
ABSTRACTThe study concerns with the slang words used in the Fate of the Furious movie. The studyaims to analyze the types of slang, the meaning of slang and the function of slang used in Fateof the Furious movie. This study used qualitative approach and the data collection was basedon observation method by downloading the movie and movie script, watching the movie,looking through the scene and taking note. The theoretical framework of the study is based onLeech’s five types of language function (1981) and the theory proposed by Chapman (2007)about two two kind of slangs: primary slang and secondary slang. The meanings of slang weretaken from some online dictionaries that related to slang. This study reveals that there are 25slangs which is found in Fate of the Furious movie. From the data, there are 22 primary slangsand 3 secondary slangs found. The meaning of slang mostly related to informational functionwhich is focused on the speaker tends to inform something to the other characters in the movie.From the analysis of the meaning, it can be concluded that the meanings of slang words vary.Keywords: slang, types, meaning, function, Fate of the Furious movie.ABSTRAKStudi ini berkaitan dengan kata gaul dan yang terjadi dalam film Fate of the Furious. Penelitianini bertujuan untuk menganalisis jenis-jenis bahasa gaul, makna bahasa gaul, dan fungsibahasa gaul yang digunakan dalam film Fate of the Furious. Penelitian ini menggunakanpendekatan kualitatif dan pengumpulan datanya berdasarkan metode observasi denganmengunduh film dan naskah film, menonton film, melihat-lihat adegan dan mencatat. Teoriyang digunakan dalam penelitian ini didasarkan pada Leech (1981) tentang lima jenis fungsibahasa dan juga menggunakan teori yang dikemukakan oleh Chapman (2007) tentang dua jenisbahasa gaul: bahasa gaul primer dan bahasa gaul sekunder. Makna bahasa gaul diambil daribeberapa kamus online yang terkait dengan bahasa gaul. Studi ini mengungkapkan bahwa ada25 bahasa gaul yang ditemukan dalam film Fate of the Furious. Dari data tersebut ditemukan22 bahasa gaul primer dan 3 bahasa gaul sekunder. Makna bahasa gaul yang sebagian besarterkait dengan fungsi informasional yang difokuskan pada pembicara cenderungmenginformasikan sesuatu kepada karakter lain dalam film. Dari analisis makna tersebutdapat disimpulkan bahwa makna bahasa gaul itu bermacam-macam.Kata kunci: gaul, jenis, makna, fungsi, film Fate of the Furious.